Analysis of internal flow characteristics and entropy generation of low head bulb tubular pump - Tian, Xinyi; Cheng, Li; Jiao, Weixuan; Wang, Yuqi; Luo, Can (Frontiers in Energy Research, 2023)
Based on CFX software of ANSYS platform, the SST k-ω turbulence model is selected by comparing the numerical simulation results obtained by SST k-ω and RNG k-ε turbulence models with the experimental results. With the help of the flow line diagram and turbulent kinetic energy diagram of the whole flow channel of the pump device, the flow components of the pump device under different working conditions are analyzed, and the pressure and velocity distribution at the impeller and guide vane are analyzed by pressure cloud diagram and velocity cloud diagram. Based on the principle of entropy production, the wall entropy production and the distribution of mainstream entropy production at the impeller and guide vane parts are analyzed.